Pain control and neonatal outcomes in 211 women under epidural anesthesia during childbirth at high altitude in Qinghai, China - Wang, Pengxia; Li, Kaihui; Wu, Dongliang; Cheng, Sen; Zeng, Yinying; Gao, Peng; Wang, Zhibing; Liu, Shanshan (Frontiers in Medicine, 2024)
Background High altitudes are characterized by low-pressure oxygen deprivation. This is further exacerbated with increasing altitude. High altitudes can be associated with reduced oxygenation, which in turn, can affect labor, as well as maternal and fetal outcomes. Epidural anesthesia can significantly relieve labor pain. This study aimed to assess the effects of elevation gradient changes at high altitude on the analgesic effect of epidural anesthesia, labor duration, and neonatal outcomes. Methods We divided 211 women who received epidural anesthesia into groups according to varying elevation of their residence (76 in Xining City, mean altitude 2,200 m; 63 in Haibei Prefecture, mean altitude 3,655 m; and 72 in Yushu Prefecture, mean altitude 4,493 m). The analgesic effect was assessed using a visual analog scale (VAS). Labor duration was objectively recorded. The neonatal outcome was assessed using Apgar scores and fetal umbilical artery blood pH. Results VAS scores among the three groups did not differ significantly (p > 0.05). The neonatal Apgar scores in descending order were: Xining group > Haibei group > Yushu group (p < 0.05). The stage of labor was similar among the three groups (p > 0.05). Fetal umbilical artery blood pH in descending order were: Xining group > Haibei group > Yushu group (p < 0.05). Conclusion Elevation gradient changes in highland areas did not affect the efficacy of epidural anesthesia or labor duration. However, neonatal outcomes were affected.